Satellite Derived Bathymetry (SDB) and Safety of Navigation - Mavraeidopoulos, Athanasios K.; Pallikaris, Athanasios; Oikonomou, Emmanouil (The International Hydrographic Review, 2017)
This paper reviews the use of Satellite Derived Bathymetry (SDB) technology to derive depths from remote sensed (RS) data and how this technology can be used to address crucial aspects of safety of navigation. The estimation of bathymetric depth using optical RS techniques has advantages and disadvantages. Using imagery techniques, depths can be determined quickly over large remote coastal areas. These areas can however consist of dangerous hazards, submerged objects and steep seabed morphology. SDB processing techniques introduces new perspectives to potentially improving safety of navigation charting. The feasibility of deriving bathymetry from remote sensed images, requires that the accuracy of such data should be evaluated and an assessed in terms of how this data can be used and depicted in nautical chart production. The parameters associated with SDB capabilities that contribute to cartographic production are further discussed and evaluated against current IHO Standards.